The Effect of Postpartum Body Condition on the First Oestrus after Calving on the First Simmental Cross (G1) - S. Syafrizal; John Hendri (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
The body's condition after calving affects the return of Oestrus postpartum, and minimizing this period is important for several reasons. The study aimed to determine the effect of postpartum body condition on the first Oestrus on the first Simmental-cross (G1) carried out in Koto XI Tarusan and Bayang sub-districts, Pesisir Selatan District, West Sumatra province. The body condition of beef cows during calving dramatically impacts subsequent reproductive performance. The postpartum interval is the time from calving to first Oestrus after calving. Body condition postpartum affected the next first Oestrus. This research was conducted by survey method, using 83 G1, which were grouped based on thin (28 head), moderate (39 head), and fleshy (16 head). The detection of Oestrus is carried out starting after calving until the symptoms of Oestrus using a